USABILITY OF HONEYPOTS IN KENET MEMBER INSTITUTIONS IN WESTERN KENYA AS PROACTIVE DETECTION TOOLS FOR MONITORING CYBER RELATED INCIDENCES - Ogada, Peter Odhiambo; Raburu, George; Liyala, S; Okelo, N. B (IJRDO -Journal of Computer Science Engineering, 2015)
With the advent of the ever changing technology and the intense sophistication in methods andmeans of committing illegal activities, crime is no longer narrowly defined vies-a-vie the law butthere is need to be able to handle technologically oriented crimes commonly referred to asCybercrimes. Cybercrimes are crimes that involve the use of computers to undertake illegal.Collection of statistics associated with cybercrimes can be quite tricky and daunting, since theircollection and tabulation can only be done when aggrieved parties report them. Some of theseillegal activities that constitute cybercrimes include, but not limited to, creation of counterfeitcurrency or official documents using computer scanners and graphics programs, embezzlementof funds using computers to skim very small sums of money from a large number of accounts,distribution of child pornography on the Internet, and theft of digital property. Other crimes thatcan also be committed include fraud, hate crimes, stalking, gambling, hacking; spread ofmalware, phishing, spamming, Botnet attacks, DDoS attacks, espionage and money laundering.In this paper we present results on usability of HoneyPots in KENET member institutions inwestern Kenya as proactive detection tools for monitoring cyber related incidences.